DIGITAL ENTREPRENEURSHIP AND BUSINESS IN THE FIELD OF INFORMATION TECHNOLOGY - Fomichov, Kostiantyn; Riabovolyk, Tetiana (European Science, 2025)
The section is devoted to an in-depth study of the main directions of entrepreneurship development in the field of information technology and an analysis of current trends in the digital transformation of business. The paper reveals the key components of